Information dissemination in mobile social networks with gossip algorithms. (2016) - Yang, Bo; Liu, Demin; Zhang, Wenfeng
This paper studies the information dissemination problem in the mobile social network, which comprises a set of smart phones and works in a distributed manner. Gossip algorithms are used to spread information over the mobile social network with simplicity and robustness. Two typical scenarios of information dissemination are analysed. The corresponding upper bounds on the convergence time are derived, which show the relationship between mobility of users and convergence rate of gossip algorithms. The performances of gossip algorithms are examined in both scenarios. Simulation results indicate that the growth of communication cost is almost linear when the scale of mobile social networks becomes larger, which is a quite encouraging result for application.